8 case studies from China : developing skills for employability with German partners - Niediek, Silvia [Verfasser] (Bundesinstitut für Berufsbildung, 2021)
The "Developing Skills for Employability with German Partners – 8 Case Studies from China " brochure presents eight vocational education and training success stories of German providers in China. (BIBB-Doku)
Keywords: I 1 Internationale Berufsbildung; I 2.3.4 Asien; 370; 330; Berufsbildung; Internationale Zusammenarbeit; Weiterbildung; Berufsschullehrer; Industrie 4.0; Bundesrepublik Deutschland; China